Hosting Tour de France under COVID-19: Bargain or burden for new stage cities? - Herzet, C. (Umeå University Department of Geography, 2021)
The Tour De France (TDF) is the third largest sporting event in the world and the biggest cycling race in terms of popularity and prestige. The event generates global media exposure and attracts millions of short-and long-term visitors each year, thus, TDFis extremely appealing for communities in search of profits. Using Linear Directional Mean (LDM) and semi-structured interviews (community and organization sides), this paper analyze show TDF has spatially evolved through time by comparing the 2021 race track to other time intervals. Additionally, reasons of the potential shift in terms of spatial distribution are investigated considering current issues due to the COVID-19 pandemic that has severely affected the tourism sector and therefore, the benefits that communities were expecting to perceive by hosting TDF. Findings showed that the 2021 route deviated from previous editions time of the TDF history including 10 new stage cities that never hosted the event before.The respondent from the organization indicated the pandemic only indirectly affected the TDF routeand that the location of the Grand Départas well as the main internal constraints imposed to the organizers are key elements in the spatial distribution of the event. Interviewed communities acknowledged that there was risk while hosting TDF this year due to potential restrictive measures. However, they recognized that benefits brought by the race largely overweight potential negative impacts from the epidemic. Indeed, TDF remains a wayto bring economic benefits, social cohesion, happiness, pride and satisfaction to hosting cities at a time when the tourism industry is at a standstill.